La sensibilisation à l'interculturel dans l'enseignement de l'anglais à l'école primaire : observations en CE1 et CE2 - Michèle Catroux (Recherches en didactique des langues et des cultures)
This article aims at analysing the potential of raising language and culture awareness during the very first lessons of foreign language teaching in years 2 and 3. Classroom interactions have been analysed according to Byram's model so as to identify the components of a metalinguistic process. We will highlight the key elements of such an approach in the construction of an intercultural competence which would not only rely upon knowledge but rather upon the development of existential competence, skills and know-how.